2023
DOI: 10.1007/s11356-023-25661-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monosodium glutamate on fetal development and progesterone level in pregnant Wistar Albino rats

Abstract: Monosodium glutamate (MSG) is a widespread flavor enhancer and stabilizer in manufactured or packaged foods that possess myriad adverse effects. This study aimed to evaluate the effect of MSG on placental progesterone receptors and fetal development. Thirty pregnant Wistar Albino rats were divided into three groups (ten/each). The control group (G1) gavaged distilled water only, low-dose treated group (G2) gavaged 3 g/kg MSG, and high-dose treated group (G3) gavaged 6 g/kg MSG from 1st to 18th days of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 86 publications
0
3
0
1
Order By: Relevance
“…Progesterone has an essential role in maintaining pregnancy. 20 If the hormone progesterone is insufficient, it will cause continuous uterine contractions, leading to embryo implantation failure and abortion. 21 The hormone estrogen plays a role in maintaining the corpus luteum to keep secreting progesterone.…”
Section: Resultsmentioning
confidence: 99%
“…Progesterone has an essential role in maintaining pregnancy. 20 If the hormone progesterone is insufficient, it will cause continuous uterine contractions, leading to embryo implantation failure and abortion. 21 The hormone estrogen plays a role in maintaining the corpus luteum to keep secreting progesterone.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the safety and toxicity of MSG have become controversial due to reports of adverse responses in individuals who have consumed MSG-containing foods. Numerous studies have confirmed the harmful effects of MSG [9]. MSG has been linked to headaches, nausea, diarrhea, irritable bowel syndrome, asthma symptoms in asthmatic patients, and panic attacks [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mondal et al ( Mondal et al, 2017 ) reported that MSG suppresses the female reproductive function by impairing the functions of ovary and uterus. Also, MSG during pregnancy adversely influences fetal growth and skeletal development causing several biochemical and histological changes to the maternal and fetal liver and kidney tissues ( Shosha et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%